Links between airborne microbiome, meteorology, and chemical composition in northwestern Turkey - Lang-Yona, Naama; Ozturk, Fatma; Gat, Daniella; Akturk, Merve; Dikmen, Emre; Birgül, Aşkın (Elsevier, 2020)
The composition of atmospheric aerosols is dynamic and influenced by their emission sources, organic and inorganic composition, transport pathways, chemical and physical processes, microorganisms' content and more. Characterization of such factors can improve the ability to evaluate air quality and health risks under different atmospheric scenarios. Here we investigate the microbial composition of the atmospheric particulate matter (<10 mu m; PM10), sampled in Bolu, Turkey, and the linkage to the chemical composition changes, and different environmental factors. We showdistinct differences between aerosol composition of different sources and air-mass transport patterns, sampled in July-August 2017 and in February 2018. The summer samples had a typical northern component air mass trajectories and higher local wind speed. They were characterized by high PM10 levels, marine and mineral dust tracers and high relative abundance of Ascomycota, suggesting long-range transport of the particles from remote sources. In contrast, samples collected in February were characterized by a dominant contribution of southern air masses, and low wind speed. They had low PM10 values, higher relative abundance of antibiotic resistance genes and anthropogenic ions related to local industries and farming, suggesting a dominance of local sources. With the microbiome analyses reported here for the first time for this region, we show good agreement between airborne microbial composition, aerosol mass load, chemistry, and meteorology. These results allow better air quality evaluation and prediction capabilities. (C) 2020 Elsevier B.V. All rights reserved.
lang-yona, naama/0000-0002-2650-2127
Keywords: Bioaerosol; Long-range microbial transport; Airborne microbiome; Air quality; Antibiotic resistance genes